Foliar Silicon Application in the Era of Climate Change as a Part of Strategy to Reduce Water Requirements in Mediterranean Viticulture - Lia-Tânia Dinis; Natália Mota; Sandra Martins; António Castro Ribeiro; José Moutinho-Pereira; Sandra Pereira (Horticulturae)
Rising temperatures and water scarcity due to climate change are significant challenges for Mediterranean viticulture, particularly in the Douro Valley, a prominent winemaking region. Silicon (Si) has gained attention as a potential solution for mitigating these environmental stresses, especially in areas with limited water resources. This study explores the foliar application of Si as a promising strategy to reduce water requirements in vineyards, specifically for the Touriga Franca variety, thereby supporting more sustainable water use. Four treatments were tested: non-irrigated control (C−), an irrigated control under a deficit irrigation regime (25% ETc; C+), and two Si concentrations (7% Si-Si1 and 20% Si-Si2) applied to non-irrigated plants. Results demonstrate that Si-treated plants improved physiological resilience, as evidenced by enhanced photosynthetic efficiency, greater water-use efficiency, and higher biochemical quality in both leaves and berries. Additionally, Si application increased leaf flavonoids and simultaneously improved must composition due to its overall influence on vine physiology, indicating its potential as a sustainable alternative to irrigation for reducing summer stress. This research suggests that foliar Si application could be a valuable, eco-friendly strategy to support sustainable viticulture under increasingly arid conditions, reducing the irrigation needs.